EMERGENCES OF GULON INFORMAL SETTLEMENT IN SURAKARTA CITY: PERSPECTIVES ON THE PRODUCTION OF SPACE AND RHYTHMANALYSIS - Yosua Wiba Aguntar; Hikari Dwi Saputro (GeoEco, 2024)
Increasing population growth and limited residential land occur in most urban areas in Indonesia. The government has well-observed regional spatial planning (RTRW) and regulations, but there are often deviations, such as the emergence of informal settlements. This study seeks to clarify the background of the establishment of informal settlement through the production of space theory and identify how society shapes the rhythm of life in producing space. Data collection is carried out by observation, interview, participatory mapping, and temporal imagery. This research uses progressive regressive methods with the production of space theory perspective and rhythmanalysis. Rhythmanalysis is used to complement the exposition of the production of space theory. It is known that the settlement space began to be formed in 2004. Residents interpret the Gulon informal settlement location as a strategic and effective cheap livelihood location. This choice of place to live is further strengthened by the similarity of the community's economic conditions which are increasingly deteriorating, made worse by the impact of the Covid-19 pandemic. This situation encourages interaction in the rhythm of people's lives so that the concept of residential space is formed. Polyrhythmics strengthen the phenomenon of space utilization.